The people of the book and the camera : photography in the Hebrew novel - Amihay, Ofra (Judaic traditions in literature, music, and art., 2022)
"'The People of the Book and the Camera' is a study of avant-garde novels which include photographs in their pages, this book suggests that the combination of visual and verbal narration in Israeli novels allows minor voices to emerge, representing new perspectives in Israeli culture"--